2022
DOI: 10.1021/acs.jpca.2c01761
|View full text |Cite|
|
Sign up to set email alerts
|

Rotational and Vibrational Spectra of the Pyridyl Radicals: A Coupled-Cluster Study

Abstract: Pyridyl is a prototypical nitrogen-containing aromatic radical that may be a key intermediate in the formation of nitrogen-containing aromatic molecules under astrophysical conditions. On meteorites, a variety of complex molecules with nitrogen-containing rings have been detected with nonterrestrial isotopic abundances, and larger nitrogen-containing polycyclic aromatic hydrocarbons (PANHs) have been proposed to be responsible for certain unidentified infrared emission bands in the interstellar medium. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 80 publications
2
5
0
Order By: Relevance
“…31,[35][36][37]64 The heat of reaction D r H1 for (4) at 298 K ranges from 0.8 to 1.1 eV depending on the isomer. Meyer et al 14 Taking the FWHM of bands into account, the IE of the X +1 A 0 ' X 2 A 0 transition is determined to be 7.70 AE 0.02 eV. The calculated IE is 7.72 eV for oB97X-D3 and 7.61 eV for CCSD(T) and is in agreement with the experimental IE.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…31,[35][36][37]64 The heat of reaction D r H1 for (4) at 298 K ranges from 0.8 to 1.1 eV depending on the isomer. Meyer et al 14 Taking the FWHM of bands into account, the IE of the X +1 A 0 ' X 2 A 0 transition is determined to be 7.70 AE 0.02 eV. The calculated IE is 7.72 eV for oB97X-D3 and 7.61 eV for CCSD(T) and is in agreement with the experimental IE.…”
Section: Resultssupporting
confidence: 65%
“…The neutral geometry on the DFT level of p-pyridyl is in agreement with the CCSD(T) geometry. 14 The bond lengths differ by a maximum of 0.005 Å and the bond angles by a maximum of 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most exothermic reaction for this set corresponds to the formation of 1-pyridyl. The rotational and vibrational spectra of pyridyl radicals was recently reported using vibrational perturbation theory (VPT2) (Meyer et al, 2022) using highly correlated coupled cluster methods (CCSD(T)/ANO0). In their study, the authors reported that the 1-pyridyl radical is more stable by 4.14-5.57 kcal mol −1 with respect to 2-3-pyridyl, in very good agreement with our values of ∼ 5.7 kcal mol −1 .…”
Section: Abstraction Of H From Pyridine: Hydrogen Isocyanide Formationmentioning
confidence: 99%
“…Examples of other novel molecules with potential astrochemical significance include 2-aza-1,3-butadiene, the C 7 H 5 radical, functionalized buckyballs in the form of C 60 O + and C 60 OH + , the 1-quinolinium (C 9 H 7 NH + ) cation along with its corresponding neutral and hydrogenated radicals, cyano-cyclopentadiene ions, the simplest aminooxycarbene in aminohydroxymethylene (H 2 N–C̈–OH), 1-cyanocyclobutene (C 5 H 5 N), monocyclic carbon ring cations of the form C 2 n + , the phenalenyl radical, and isomers of the PAH C 16 H 10 + . Purely theoretical studies are providing characterization for other unique molecules including glycolic acid, pyridyl radicals, and diazirine along with its cyclic isomers . Additionally, the molecular structure and spectra of noncovalent interactions are also characterized through a mixture of theory and experiment for glycerol–water clusters, HCN and CH 3 Cl clusters, and complexes of NH 3 ···CO …”
mentioning
confidence: 99%